PEMANFAATAN MINYAK JELANTAH SEBAGAI BAHAN DASAR PEMBUATAN SABUN CUCI DAN LILIN - Ayulia Dwi Rizky; Citra Amalia Hapsari; Dhiya Salsabila Fitria; Nasruddin Najib; Anggitia Putri Pertiwi (JPS : Jurnal Pengabdian Serulingmas, 2022)
Oil can be sourced from plants, for example olive oil, corn oil, coconut oil, and sunflower seed oil. The need for cooking oil is quite large, causing people to use cooking oil repeatedly to save costs. Cooking oil that has been used repeatedly will experience a decrease in the quality of the cooking oil marked by a dark color change, the aroma becomes less pleasant, the free fatty acid content and the peroxide number are high. The purpose of this activity is to provide education to mothers about the dangers of using used cooking oil repeatedly and also to provide solutions so that used cooking oil can be reused into products, such as laundry soap and candles. The targets for this activity are the women of Denggung Hamlet, Tridadi Village, Sleman Regency, DI Yogyakarta. The participants from the practice of making soap and candles were 5 people. This activity consists of lectures as well as discussions, demonstrations and hands-on practice. This activity can be followed well and enthusiastically by the mothers. Through the practice of making soap and candles, it is hoped that the Dusun Denggung mothers can protect the environment and can utilize/recycle household waste into useful products.